Pengaruh Teknologi Informasi terhadap Publikasi Karya Ilmiah Mahasiswa Pendidikan Agama Islam - St. Wardah Hanafie Das; Jumsir Jumsir; Anita. S; Muhammad Rizal; Hasriyanti Hasan (FKIP UNSULTRA, 2025)
The development of information technology has brought significant changes to higher education, including in the publication of student scientific papers. Islamic Religious Education (PAI) students are required not only to master the substance of Islamic scholarship but also to possess digital literacy skills to support academic productivity, particularly in scientific publications. This study aims to analyze the influence of information technology on the publication of Islamic Religious Education (PAI) students' scientific papers. The research method used was a quantitative approach with a survey design. The study population was PAI students at Islamic universities, with the sample determined using a purposive sampling technique. The research instrument was a questionnaire measuring information technology utilization and the level of student scientific paper publication. Data were analyzed using descriptive and inferential statistics through simple regression tests. The results showed that information technology had a positive and significant effect on the publication of Islamic Religious Education (PAI) students' scientific papers. The use of online journal platforms, reference management applications, and access to digital literature sources were proven to increase student motivation, quality, and quantity of scientific publications. These findings confirm that the integration of information technology in the learning and academic development of PAI students is essential for fostering a culture of writing and sustainable scientific publication. Therefore, universities need to optimize digital literacy training and information technology-based scientific publications for PAI students.